Regulated Alternative Splicing of Drosophila Dscam2 Is Necessary for Attaining the Appropriate Number of Photoreceptor Synapses. Issue 2 (1st February 2018) - Kerwin, Sarah K; Li, Joshua Shing Shun; Noakes, Peter G; Shin, Grace Ji-eun; Millard, S Sean
Abstract: How the brain makes trillions of synaptic connections using a genome of only 20, 000 genes is a major question in modern neuroscience. Alternative splicing is one mechanism that can increase the number of proteins produced by each gene, but its role in regulating synapse formation is poorly understood. In Drosophila, photoreceptors form a synapse with multiple postsynaptic elements including lamina neurons L1 and L2. L1 and L2 express distinct isoforms of the homophilic repulsive protein Dscam2, and since these isoforms cannot bind to each other, cell-specific expression has been proposed to be necessary for preventing repulsive interactions that could disrupt the synapse. Here, we show that the number of synapses are reduced in flies that express only one isoform, and L1 and L2 dendritic morphology is perturbed. We propose that these defects result from inappropriate interactions between L1 and L2 dendrites. We conclude that regulated Dscam2 alternative splicing is necessary for the proper assembly of photoreceptor synapses.